Aceh education system: can situational leadership style improve students' learning process? - Priyanto, Heri (Universiti Putra Malaysia, 2010)
Teachers, a lowest level of education need to maximize their effort for maximizing completion rate at their school. It refers to national exam as a part of important role to determine students' completion. Some times efforts was opposite with the philosophy of education and assessment itself. The function of national exam as an instrument to measure the teacher effectiveness on teaching and learning has been changing from constructivist and direction approach to drilling approach. The objective of this paper is to analyzethe chance of using situational leadership style at the classroom level. From my perspective, the implementation of situational leadership style in the classroom can improve students' learning process since the teacher style is based on the students' condition. Teachers' style can be different based on the learning maturity of students. By increasing maturity of students, teachers' style change from telling style to delegating style. This type of leadership also useful in bringing Islamic value to the student, especially in the context of implementation qanun no 5/2008 about Aceh education system.